Lupin poisoning: a review - Bloothooft, Meye; Cremers, Pien; Güven, Sükriye; Stoutjesdijk, Stijn J.; Jiron, Mara; Wessel, Mark; Van Der Heyden, Marcel A. G. (Frontiers in Toxicology, 2025)
IntroductionLupin beans are the seeds of plants from the Fabaceae family. These beans are rich in protein and used for human consumption for several millennia. Their popularity is still increasing. Some species produce beans with high alkaloid contents, specifically of spartaine and lupanine. Without proper processing, consuming these beans can result in lupin poisoning that causes anticholinergic syndrome. We systematically analyzed all case reports describing lupin poisoning in humans in order to define most observed clinical findings, treatment options and outcome.MethodsWe screened Pubmed and Google scholar for human case reports on lupin poisoning. Obtained full-text papers in any language were screened for eligibility. Demographics, time-to-symptoms, treatment and outcome were analyzed. Symptoms were categorized using the ICD11 classification.ResultsTwenty-seven case reports describing 33 patients were obtained. Poisoning occurred in all age groups and sexes equally. Most frequent symptoms were bilateral mydriasis (n = 25), xerostomia (n = 25), blurred vision (n = 17), lightheadedness (n = 14), weakness (n = 11). Onset of symptoms was typically within 60 min. In most cases no treatment was required, and symptoms resolved within 24 h after which patients were discharged. Two of four children in the cohort required ICU admission and one died.DiscussionLupin poisoning is rare and requires most often a conservative clinical approach. However, in children the effects are more severe than in adults. Frequency of lupin poisoning may rise due to increased popularity of the beans as an alternative protein source.